2014
DOI: 10.4330/wjc.v6.i7.675
|View full text |Cite
|
Sign up to set email alerts
|

Is cardiac MRI an effective test for arrhythmogenic right ventricular cardiomyopathy diagnosis?

Abstract: AIM:To evaluate the referrals with suspected arrhythmogenic right ventricular cardiomyopathy (ARVC) and compare cardiac MR (cMR) findings against clinical diagnosis. METHODS:A retrospective analysis of 114 (age range 16 to 83, males 55% and females 45%) patients referred for cMR with a suspected diagnosis of ARVC between May 2006 and February 2010 was performed after obtaining institutional approval for service evaluation. Reasons for referral including clinical symptoms and family history of sudden death, ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Left ventricular (LV) or biventricular involvement are increasingly identified in ARVD/C patients 4 . Cardiac magnetic resonance (CMR) is a valuable diagnostic tool for ARVD/C due to the high negative predictive value, which can identify mild LV impairment and thus has a significant impact on clinical decision-making 5,6 . Prior studies have demonstrated that CMR evidence of LV involvement is a strong independent predictor of hard cardiac events in the entire population, including patients with a definite, borderline, or possible ARVD/C diagnosis 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Left ventricular (LV) or biventricular involvement are increasingly identified in ARVD/C patients 4 . Cardiac magnetic resonance (CMR) is a valuable diagnostic tool for ARVD/C due to the high negative predictive value, which can identify mild LV impairment and thus has a significant impact on clinical decision-making 5,6 . Prior studies have demonstrated that CMR evidence of LV involvement is a strong independent predictor of hard cardiac events in the entire population, including patients with a definite, borderline, or possible ARVD/C diagnosis 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Over the last years, cardiac magnetic resonance (CMR) imaging has gained popularity as the modality of choice for the evaluation of ARVD/C, allowing for noninvasive morphological and functional evaluation, as well as tissue characterization in a single investigation . CMR is especially useful for evaluation of the atria, which are difficult to visualize using other imaging techniques .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the sensitivity of CMRI in children is low because arrhythmic presentations precede structural changes 38 . High negative predictive value of Gadolinium-enhanced CMRI makes it a good choice as a rule-out imaging test for evaluation of structural and functional abnormalities in patients suspected to have ARVC 39 .…”
Section: Discussionmentioning
confidence: 99%